Education and freedom of choice: Evidence from arranged marriages in Vietnam - M. Shahe Emran; Fenohasina Maret-Rakotondrazaka; Stephen C. Smith (Institute for the Study of Labor (IZA), 2012)
Using household data from Vietnam, we provide evidence on the effects of education on freedom of spouse choice. We use war disruptions and spatial indicators of schooling supply as instruments. The point estimates indicate that a year of additional schooling reduces the probability of an arranged marriage by about 14 percentage points for an individual with eight years of schooling. We also estimate bounds on the effect of education on arranged marriage when exclusion restrictions are violated locally (the lower bound is six to seven percentage points). The impact of education is strong for women, but significantly weaker for men.
Keywords: I2; O12; D1; J12; 330; arranged marriage; education; schooling; freedom of choice; development; Vietnam; Red River delta; labour markets; social interactions; Ehe; Bildungsniveau; Freiheit; Soziale Beziehungen; Schulbesuch; Vietnam